2000
DOI: 10.1590/s0074-02762000000100001
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of mosquitoes (Diptera: Culicidae) in areas of Serra do Mar State Park, State of São Paulo, Brazil. I - Monthly frequency and climatic factors

Abstract: The ecology of mosquitoes were studied (Diptera: Culicidae) in areas of Serra do Mar State Park, State of São Paulo, Brazil. Systematized monthly human bait collections were made three times a day, for periods of 2 or 3 h each, in sylvatic and rural areas for 24 consecutive months (January 1991 to December 1992). A total of 24,943 specimens of adult mosquitoes belonging to 57 species were collected during 622 collective periods. Coquillettidia chrysonotum was the most frequent collected mosquito (45.8%) follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1
8

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 15 publications
(31 reference statements)
3
20
1
8
Order By: Relevance
“…Similar studies (13) (14) have reported that rainfall primarily controls the availability of breeding sites and the abundance of mosquitoes. However, the early formation of the reservoir during Phase II resulted in the fl ooding of vast areas of forest and the presence of decaying vegetation around the reservoir, which signifi cantly favored An.…”
Section: Studies Conducted Near the Itaipu Hydroelectric Plantsupporting
confidence: 54%
“…Similar studies (13) (14) have reported that rainfall primarily controls the availability of breeding sites and the abundance of mosquitoes. However, the early formation of the reservoir during Phase II resulted in the fl ooding of vast areas of forest and the presence of decaying vegetation around the reservoir, which signifi cantly favored An.…”
Section: Studies Conducted Near the Itaipu Hydroelectric Plantsupporting
confidence: 54%
“…6 As formas adultas de Kerteszia dominam entre os Culicidae em matas primitivas. 9,10,12,14,15 Em áreas de restinga, An. bellator domina sobre An.…”
Section: Abstract: Anopheles Insect Vectors Ecology Vertical Distrunclassified
“…Entretanto, os dados disponíveis sobre a ecologia dessas duas últimas não permitem maiores observações sobre esses índices. Guimarães et al 11 (2000) relataram a presença do An. fluminensis nos meses mais frios no PESM.…”
Section: Resultsunclassified
“…Guimarães & Arlé 10 (1984), Guimarães et al 11 (2000) Tabela -Coeficiente de correlação linear entre a incidência das diferentes espécies de culicídeos encontrados no Parque Nacional da Serra da Bocaina e as medições obtidas para temperatura, umidade relativa e pluviosidade. (r 0,1(2) 10 = 0,497).…”
Section: Resultsunclassified
See 1 more Smart Citation